Breed differences in susceptibility of sheep to Haemonchus contortus - Singh, Satyaveer; Yadav, C L (The Indian Journal of Animal Sciences, 2012)
Susceptibility of Nali (group 1), 50% Nali x 50% Russian Merino/Corriedale (group 2) and 37.5% Nali x 62.5% Russian Merino/Corriedale (group 3) lambs to experimental Haemonchus contortus infection was investigated. Faecal egg output, worm counts and haematological values indicated that groups 1 and 3 lambs were more susceptible than group 2 lambs. Group 2 lambs had significantly (P<0.05) higher body weights than those of group 3 lambs. Estimations of total serum protein, calcium, phosphorus and iron showed significantly higher decrease in group 3 when compared to groups 1 and 2 lambs. Two lambs of group 3 suffered with severe anaemia and emaciation.